A informação contábil e a teoria de agência: um estudo da assimetria informacional em companhias abertas, listadas no novo mercado da Bovespa - Pires, Rodolpho Gonçalves (2008)
This study analyzes the agent s perception of Accounting as a mechanism for reducing information asymmetry between the Principal and itself. The agents considered in this study were the administrators of all thirty-six domestic public companies listed on the special market segment with additional requirements related to corporate governance of the Sao Paulo Stock Exchange in Brazil, called Novo Mercado da BOVESPA , as of October 2006. In view of the widespread and growing concerns around corporate governance and the relevance of accounting information, this study s empirical research is based on two assumptions that (i) there are information asymmetry-related problems between agent and principal, and (ii) accounting information, considering its major objective, acts as an information asymmetry reduction mechanism between principal and agent. The primary objective of this study was to analyze the relation between Agency Theory and Accounting, on matters related to information asymmetry between agent and principal, as part of the agency conflicts. The secondary objectives were to (i) question this relation on domestic companies listed on the special market segment with additional corporate governance requirements of the Sao Paulo Stock Exchange in Brazil, (ii) analyze the role of accounting information in the agency relations of those companies, (iii) verify the evaluation made by the agents in relation to the importance of Accounting to the information asymmetry reduction, (iv) relate Accounting and Agency Theory in domestic public companies listed in this market segment, and (v) contribute to the development of the positive approach in accounting research in Brazil. A questionnaire was applied as means of data collection for the realization of the empirical research. The instrument was sent to each one of the thirty-six responsible for the investors relations department of these companies. It represents the total number of companies listed in this special market segment up to October 2006. At the end of the researching phase, according to the working chronogram, a 53% responses rate was achieved. Analysis of the compiled data suggests that there is an alignment with the aforementioned assumptions. The majority of respondents perceive the existence of information asymmetry problems between principal and agent. Similarly, the majority of participants evaluated Accounting as a mechanism that enables the reduction of information asymmetry problems between agent and principal